Wastewater treatment by microalgae-bacteria co-culture system - Samsudin, Amirah; Azmi, Azlin Suhaida; Mohd Nawi, Mohd Nazri; Abdul Halim, Amanatuzzakiah (Malaysian Society for Microbiology, 2018)
Aim: Microalgae is one of the bioremediation agents in wastewater treatment due to its ability to degrade nutrients and organic compounds. Several studies reported that co-cultivation of microalgae and bacteria, i.e. Microalgae Growth Promoting Bacteria (MGPB) could improve the nutrients removal process. This MGPB helps to degrade complex nutrient compounds into smaller components before being taken up by microalgae. The objective of this study is to investigate the effectiveness of co-cultured (microalgae and bacteria) system compared to axenic microalgae system in the removal of major nutrients (ammonium and phosphorus) and chemical oxygen demand (COD) in synthetic wastewater.